2014
DOI: 10.2166/wst.2014.034
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrospun polyurethane nanofibre membrane – production parameters and suitability for wastewater (WW) treatment

Abstract: The aim of this study was to investigate the suitability of a novel electrospun polyurethane nanofibre material for water-treatment purposes. Bacterial removal efficiency was tested in the laboratory by filtering artificial water spiked with Escherichia coli through a 0.25 µm nanofibre membrane. The results were compared with those obtained using a commercial microfiltration material (MV020T) with a similar pore size (0.20 µm). Alongside the laboratory experiments, we also determined filtration efficiency with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Immobilized enzyme performance, to a great extend depends on the structure of support. Studies reveal that nano structured supports were found to preserve catalytic activity and ensure efficiency of immobilized enzyme to a great level (Lev et al 2014;Maryskova et al 2019). Likewise, nanofibrous support provides greater porosity and good interconnectivity there by acting as one of the ideal systems for immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilized enzyme performance, to a great extend depends on the structure of support. Studies reveal that nano structured supports were found to preserve catalytic activity and ensure efficiency of immobilized enzyme to a great level (Lev et al 2014;Maryskova et al 2019). Likewise, nanofibrous support provides greater porosity and good interconnectivity there by acting as one of the ideal systems for immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane filtration has recently become a good alternative to more commonly used water purification technologies based on chlorination or oxidation processes, mainly due to their reducing costs and high microbial removal efficacy. Besides other commercially available filtration membranes, electrospun nanofiber membranes have great potential, since they represent even more promising choices for high flux microfiltration applications (Kaur et al 2014; Lev et al 2014; Seyed Shahabadi et al 2016; Wang et al 2012). Moreover, either polymer matrix for nanofiber preparation or surface of the pristine membrane itself can be functionalized with various techniques or antimicrobial agents that suppress biofilm formation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lev, J. et al also reported using electrospinning technique to prepare PU-NFs [51]. The as-prepared nanofibers were collected on polypropylene textiles, as a range of flat sheet non-woven nanofiber membrane layers.…”
Section: Nanosynthesis Of Representative Polymers Used In Construcmentioning
confidence: 99%